Inkarnasi Sebagai Kritik Terhadap Barbarisme Digital Dalam Fenomenologi Henry dan Liturgi Katolik - Yohanes Devri Maturbongs (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2025)
This study explores the tension between religious experience in the digital era and the incarnational nature of Catholic liturgy, drawing on Michel Henry’s phenomenology of life. The migration of religiosity into digital spaces reinforces a representational logic that, for Henry, produces barbarism: a condition in which images, objects, and technological mediation displace interior life and affective self-experience. The research aims to identify how digital barbarism reshapes liturgical experience and how the mystery of the Incarnation offers a theological critique of the reduction of faith to visuality and representation. Employing a qualitative literature-based method, this study analyzes Henry’s primary writings alongside contemporary works on liturgy and incarnational theology from the past decade. Findings indicate that the digitalization of religious practices risks severing the essential relation between body, affection, and presence that grounds liturgy. The analysis shows that the Incarnation presents an alternative paradigm affirming the primacy of concrete, lived experience over technological representation. The study concludes that Henry’s phenomenology provides a precise critical framework for evaluating the theological implications of digital liturgy, while the Incarnation offers a corrective horizon restoring the embodied character of Christian faith. This research contributes to liturgical studies and Catholic religious education by articulating an ontological foundation for critiquing increasingly disembodied forms of spirituality.